Avaliação da histomorfometria do colágeno do ligamento cruzado anterior de fetos - Leitão Junior, Aurélio Frota (2024)
The ACL is the main restrictor of the anterior translation of the tibia over the femur, being responsible for 85% of the anterior stabilization of the knee. Ligaments play a vital role in maintaining the stability and normal function of musculoskeletal joints. The main types of collagen present in ligaments are type I and type III, with type I collagen predominating in 90%. The objective of this study is to evalute histomorphometry of type I and type III collagen in the anterior cruciate ligament in human fetuses. The composition of type I and type III collagen in the anterior cruciate ligament was evaluated in ten ligaments of human fetuses, of gestational age varying between 21 and 37 weeks, where the ligaments were divided into; field 1, tibial insertion of the ACL; field 2, body of the ACL; field 3, femoral insertion of the ACL. Picrosirius red was used for histological study, the images were measured through the percentage of collagen area with yellow-red birefringence compatible with type I collagen and the green-white area related to type III collagen. Type I collagen was more common in all fields studied; In field 1, a type I collagen composition averaged 65.51%, while the type III collagen composition averaged 21.03%; in field 2 it presented an average composition of type I collagen of 56.75% and type III collagen of an average of 25.44%; in field 3 it presented an average composition of type I collagen of 60.52% and type III collagen of an average of 23.54%. Therefore, type I collagen in the distal part of the anterior cruciate ligament presented a statistically significant greater relationship between type I and type III collagen than in the intermediate part of the ligament, characterizing the distal and more resistant part and the intermediate part as more elastic, due to the properties of collagens.